Triglyceride Lipase Activity and Human Platelets - Lote, Knut; Lowery, Carol (Thrombosis and Haemostasis, 1979)
The activity of triglyceride lipases in human postheparin plasma is significantly higher in platelet rich than platelet poor plasma. This holds for total activity, lipoprotein lipase (LPL) activity, and hepatic triglyceride lipase (H-TGL) activity.Gel filtration of platelet rich postheparin plasma on Sepharose 2 B will separate platelets from triglyceride lipase activity.The very small triglyceride lipase activity of isolated platelets is inhibited by 1.0 M NaCl, slightly inhibited by specific antibody to hepatic lipase, and not influenced by specific antibody to lipoprotein lipase.